  # If α and β are the Zeros of the Quadratic Polynomial f(x) = ax2 + bx + c, then Evaluate

By BYJU'S Exam Prep

Updated on: October 17th, 2023 If α and β are the zeroes of the quadratic polynomial f(x) = ax2 + bx + c, then evaluate:

(i) α − β

(ii) 1/α − 1/β

(iii) 1/α + 1/β – 2αβ

(iv) α2β − αβ2

(v) α4 + β4

If α and β are the zeroes of the quadratic polynomial f(x) = ax2 + bx + c, then we know the following basic things which can be used to find the desired results:

• α + β = -b/a
• αβ = c/a
• Quadratic polynomial can be factored as f(x) = a(x – α)(x – β)

Solution:

## (i) α − β

To find α – β, we need to know the values of α and β, which are the zeroes of the quadratic polynomial. Let’s assume the quadratic polynomial is f(x) = ax2 + bx + c, and its zeroes are α and β.

Then we know that:

α + β = -b/a

We can rearrange this equation to get:

α = -b/a – β

Now, we substitute this expression for α into the equation f(α) = 0, which gives:

2 + bα + c = 0

Substituting for α, we get:

a(-b/a – β)2 + b(-b/a – β) + c = 0

Expanding and simplifying, we get:

2 + (-2ab/a)β + (a/b)c – b/a = 0

Multiplying both sides by b/a, we get:

abβ22abβ + ac – b2 = 0

Dividing both sides by ab, we get:

β2 – (b/a)β + (c/a) = 0

This is a quadratic equation in β, with coefficients -b/a and c/a. So we can use the quadratic formula to solve for β:

β = [-(b/a) ± √((b/a)2 – 4(c/a))]/2

Once we have found the values of α and β, we can easily find α – β:

α – β = (-b/a – β) – β

α – β = -b/a – 2β

α – β = -b/a – 2[(-b/a) ± √((b/a)2 – 4(c/a))]/2

Simplifying, we get:

α – β = ±√(b2 – 4ac)/a

## (ii) 1/α − 1/β

1/α – 1/β = (β – α)/(αβ)

Using the quadratic formula, we have:

α,β = [-b ± sqrt(b2 – 4ac)]/(2a)

So, substituting the expression for α and β:

1/α – 1/β = [(b + sqrt(b2 – 4ac)) – (b – sqrt(b2 – 4ac))]/[2a(sqrt(b2 – 4ac))]

Simplifying the numerator:

1/α – 1/β = 2sqrt(b2 – 4ac)/[2a(sqrt(b2 – 4ac))]

1/α – 1/β = ±sqrt(b2 – 4ac)/c

Therefore, the correct answer for (ii) in terms of a, b, and c is:

1/α – 1/β = ±sqrt(b2 – 4ac)/c

## (iii) 1/α + 1/β – 2αβ

We can first find a common denominator for the two fractions by multiplying them by (αβ)/(αβ):

1/α + 1/β – 2αβ = (β + α) / (αβ) – 2αβ

= (β + α – 2αβ²) / (αβ)

using αβ = c/a and α + β = -b/a

1/α + 1/β – 2αβ = (-b/a) / (c/a) – 2c/a

On solving we will get,

= -(b/c + 2c/a)

Therefore, 1/α + 1/β – 2αβ = -b/c – 2c/a.

## (iv) α2β − αβ2

We can rewrite the expression α2β − αβ2 as αβ(α − β)

On putting αβ = c/a and α − β = -b/a, we get

= c/a(− b/a)

= -cb/a2

## (v) α4 + β4

Simplifying: α4 + β4 = (α2 + β2)2 – 2α2β2

α + β = -b/a

αβ = c/a

Using these values, we can find:

α2 + β2 = (α + β)2 – 2αβ

α2 + β2 = (b/a)2 – 2(c/a)

α2 + β2 = (b2 – 2ac)/a2

Substituting this back into the original identity, we get:

α4 + β4 = ((b22ac)/a2)2 – 2α2β2

α4 + β4 = (b4 – 4b2ac + 4a2c2)/a4 – 2(c/a)2

α4 + β4 = (b4 – 4b2ac + 4a2c2 – 2c2a2)/a4

Simplifying this expression, we get:

α4 + β4 = (b4 – 4b2ac + 4a2c2 – 2c2a2)/a4

α4 + β4 = (b4 – 4b2ac + 4c2(a2 – c))/a4

Therefore, the value of α4 + β4 in terms of a, b, and c is:

α4 + β4 = (b4 – 4b2ac + 4c2(a2 – c))/a4

or

α4 + β4 = (b2 – 2ac)2– 2a2c2))/a4

## If α and β are the Zeros of the Quadratic Polynomial f(x) = ax2 + bx + c, then Evaluation Answers

(i) α − β = ±sqrt(b2 – 4ac)/a

(ii) 1/α − 1/β = ±sqrt(b2 – 4ac)/c

(iii) 1/α + 1/β – 2αβ =  -b/c – 2c/a

(iv) α2β − αβ2 = -cb/a2

(v) α4 + β4 = (b2 – 2ac)2– 2a2c2))/a4

Similar Questions:

POPULAR EXAMS
SSC and Bank
Other Exams GradeStack Learning Pvt. Ltd.Windsor IT Park, Tower - A, 2nd Floor, Sector 125, Noida, Uttar Pradesh 201303 help@byjusexamprep.com